Influence of Trade War Sentiment on Stock Market and Bitcoin: A Wavelet Coherence Approach - Somasuntharam, Raja Solan; Said, Fathin Faizah; Sarmidi, Tamat; Yaakub, Mohd Ridzwan (International Journal of Economics, Management and Accounting, 2026)
The massive amount of information shared on social media regarding certain issues could influence user sentiments. This study examined the importance of users’ sentiments in Twitter platform regarding the trade war related to the S&P 500, MSCI China, and Bitcoin returns. The wavelet coherence method was utilized to examine the issue, which involved daily data observation spanning 4 March 2020 to 20 January 2021. The estimations revealed that users’ sentiments showed significant co-movement with the returns on S&P 500, MSCI China, and Bitcoin. The finding may be useful for both policymakers and investors in their efforts to create strategies to reduce market volatility, particularly in navigating through undesired future events. It can particularly assist investors in developing profitable investment strategies for volatile markets.